Pengembangan Penggunaan Energi Biomassa pada Sektor Rumah Tangga dan Dampaknya pada Beban Subsidi Elpiji dan Kesehatan Keluarga Miskin - Arif Haryana (Bappenas Working Papers, 2019)
To overcome the problem of fuel dependence from imports and reduce the burden of fuel subsidies in the APBN, starting in 2007 the Government has implemented a conversion program for fuel use in the household sector from kerosene to LPG. The program has been running successfully. However, the same problem as before reappeared. The higher LPG needs depend on imports, reaching 70 percent of total consumption. Likewise, the burden of LPG subsidies in the state budget is even higher. Indonesia has the potential to produce abundant biomass energy and has been used as household fuel, especially in rural areas. However, the utilization is still by burning firewood using traditional inefficient combustion stoves that produce air pollutant that causing a negative impact on family health. Changes in the way biomass energy are used through the transformation of biomass into pellets and the use of technology biomass stoves can overcome the problems. This paper aims to analyze and provide policy recommendations to develop biomass energy utilization in households in a healthy manner and can improve combustion efficiency. The widespread use of biomass energy by households will reduce the dependence on LPG imports and reduce the burden of subsidies in the state budget.